Activation of mouse oocytes and in vitro embryo enhancing potential of Nigella Sativa - Abdul Rahman, Suzanah; Abdul Rahman, Mohd Rahimi Ashraf; Abdul Samat, Nadia Hanis; Basha, Sadak (2015)
Objective: Aim of the present study is to optimize the development of the mouse embryo with addition of different concentrations of Nigella sativa extract in the culture. Methods: In this study, three different concentrations of Nigella sativa supplementation were used to assist in the enhancement of embryo development. G-1 media was used as a control (Group I). Groups II, III and IV were modified with the addition of Nigella sativa at low dose (5%), moderate dose (10%) and high dose (15%) respectively. Results: Results showed an increase in the number of oocytes that successfully developed into morula and blastocyst after supplementation with three different concentrations of Nigella sativa in the embryo medium. Conclusions: The outcome of the study indicated that Nigella sativa supplementation at a moderate concentration may help in the optimization of mouse embryo culture leading to an increase in the number of morulas and blastocysts.